The defect aggregation of RE3+ (RE = Y, La ∼ Lu) in MF2 (M = Ca, Sr, Ba) fluorites. (May 2020) - Ma, Fengkai; Su, Fang; Zhou, Rongfu; Ou, Yiyi; Xie, Liujing; Liu, Chunmeng; Jiang, Dapeng; Zhang, Zhen; Wu, Qinghui; Su, Liangbi; Liang, Hongbin
Graphical abstract: Highlights: Cubic and square antiprism sublattice transformation of rare-earth clusters. Coupling of electrostatic and hybridization induced strain controlled the clusters. Promising approach for up and down-conversion photoluminescence tuning. Abstract: The clustering of trivalent lanthanide-doped fluorite was divided into four stages. Characters of the first three stage discrete clusters were studied by the density functional theory (DFT) based first principles calculation in the work. The results revealed the relative stabilities of first stage C4v and C3v were intimately correlated with that of the second and third stage clusters. The more stable C4v with interstitial Fi − at the nearest site would stabilize the second cubic sublattice centers and C3v with Fi − at next nearest site for the third square antiprism clusters. The lattice mismatch and projected density of states (pDOS) results indicated that coupling of electrostatic, strain, bonding and hybridization among Fi −, RE 3+ and surrounded lattice anions controlled the site occupation and the correlations. The clusters and clustering features could be modulated and utilized to tune up- and down-conversion photoluminescence for designing of new lanthanide-doped fluorite materials.